Terapi Kelompok untuk Menurunkan Kecenderungan Perilaku Bullying Pada Siswa SMP - Chalifatiyanti, Indarsyah (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2017)
Abstract The purpose of this study was to see the effectiveness of group therapy in reducing bullying behavior among students of Among Siswa Surabaya Middle School. The subjects of this study were six students who committed bullying using purposive sampling technique. Determination of the subject is based on the results of interviews with teachers Counseling Guidance. This study uses a quantitative approach and is included in the type of experimental experimental research. The experimental design used was One Group Pretest-Postest Design. The results of data analysis using the Wilcoxon Signed Ranks Test technique obtained results of Z = -2.207, with a significance level of p = 0.024 (p˂ 0.05). This means group therapy can significantly reduce bulying behaviorKeywords: group therapy, bullying